ROLE OF IMPROVED SEEDS TOWARDS IMPROVING LIVELIHOOD AND FOOD SECURITY AT ETHIOPIA - Abebe, Girma; Alemu, Amanuel (International Journal of Research -GRANTHAALAYAH, 2017)
Seed is a key input for improving crop production and productivity. Increasing the quality of seeds can increase the yield potential of the crop by significant folds and thus, is one of the most economical and efficient inputs to agricultural development. Generation and transfer of improved technologies are critical prerequisites for agricultural development particularly for an agrarian based economy such as of Ethiopian. In Ethiopia, for instance, a unit increase in GDP derived from agriculture has a potential of reducing poverty annually by 1.66% as compared to 0.73% poverty reduction expected from non-agricultural sector. Agriculture, particularly crop farming, has a greater effect on both the rural and the urban poor who spend more than a half of their incomes on food. When there are different seed sources available and farmers get access to them there is high probability of adoption of improved varieties .An enhanced seed availability though formal or informal or both sources will improve smallholder farmer’s access to seed and enhance improved variety adoption. In practice, whenever a farmer is talking about getting a new seed it implies that she or he is deciding to adopt a new variety. The ultimate goal of a farm household in a risk prone agro-ecology is to obtain seed with characteristics suitable to farmers’ agro-ecological and socio-economic condition. Similarly, seed is pivotal in the improvement of food security and farm household livelihood.